Kemandirian Belajar Mahasiswa Dalam Perkuiahan Daring Ditinjau Dari Self Endurance - Muhammad Taufiqurrahman; Tamama Rofiqah (Institut Agama Islam Negeri Bengkulu, 2023)
Abstract: Student Learning Independence in Online Lectures in View of Self EnduranceThis research is based on the conditions of online lectures that have occurred since the emergence of Covid-19. Seeing the fact that new students have not attended face-to-face lectures at all which is assumed to have an impact on self-endurance which will also affect student learning independence. For this reason, this research was carried out using the mixed method, which combines quantitative and qualitative methods to answer the two problem formulations. The formulation of the problem is First, the correlation between learning independence and student self-endurance; Second, the role of self-endurance in student learning independence. The number of samples was 171 students consisting of 2 PTKIN campuses in Bengkulu Province. The results of the study revealed that there was a positive correlation between learning independence and student self-endurance with an r value of 0.372 which means that there is a unidirectional relationship between the two variables with a low correlation. Then there are 3 roles of self-endurance in student learning independence during online lectures, namely: 1) Stimulating endurance, 2) Self-understanding, 3) Academic success.Abstrak: Kemandirian Belajar Mahasiswa Dalam Perkuliahan Daring Ditinjau Dari Self Endurance.Â Penelitian ini didasari pada kondisi perkuliahan daring yang terjadi sejak munculnya covid-19. Melihat fakta bahwa mahasiswa baru belum sama sekali mengikuti perkuliahan tatap muka yang diasumsikan berdampak kepada self endurance atau ketahanan diri yang nantinya juga akan berpengaruh terhadap kemandirian belajar mahasiswa. Untuk itu penelitian ini dilaksanakan dengan menggunakan mix method, yaitu menggabungkan metode kuantitaif dan kualitatif untuk menjawab dua rumusan masalah. Rumusan masalahnya adalah Pertama, korelasi antara kemandirian belajar dan self endurance mahasiswa; Kedua, peran self endurance dalam kemandirian belajar mahasiswa. Jumlah sampel sebanyak 171 mahasiswa terdiri dari 2 kampus PTKIN yang ada di Provinsi Bengkulu. Hasil penelitian mengungkapkan bahwa terdapat korelasi positif antara kemandirian belajar dan self endurance mahasiswa dengan nilai r sebesar 0,372 yang berarti terdapat hubungan searah antar dua varibael dengan korelasi rendah. Kemudian terdapat 3 peran self endurance dalam kemandirian belajar mahasiswa saat perkuliahan daring yakni: 1) Memacu daya tahan, 2) Memahami diri sendiri, 3) Keberhasilan akademik..